Radioiodine plus recombinant human thyrotropin do not cause acute airway compression and are effective in reducing multinodular goiter - Albino,C.C. (2010)
Recombinant human thyrotropin (rhTSH) reduces the activity of radioiodine required to treat multinodular goiter (MNG), but acute airway compression can be a life-threatening complication. In this prospective, randomized, double-blind, placebo-controlled study, we assessed the efficacy and safety (including airway compression) of different doses of rhTSH associated with a fixed activity of 131I for treating MNG. Euthyroid patients with MNG (69.3 ± 62.0 mL, 20 females, 2 males, 64 ± 7 years) received 0.1 mg (group I, N = 8) or 0.01 mg (group II, N = 6) rhTSH or placebo (group III, N = 8), 24 h before 1.11 GBq 131I. Radioactive iodine uptake was determined at baseline and 24 h after rhTSH and thyroid volume (TV, baseline and 6 and 12 months after treatment) and tracheal cross-sectional area (TCA, baseline and 2, 7, 180, and 360 days after rhTSH) were determined by magnetic resonance; antithyroid antibodies and thyroid hormones were determined at frequent intervals. After 6 months, TV decreased significantly in groups I (28.5 ± 17.6%) and II (21.6 ± 17.8%), but not in group III (2.7 ± 15.3%). After 12 months, TV decreased significantly in groups I (36.7 ± 18.1%) and II (37.4 ± 27.1%), but not in group III (19.0 ± 24.3%). No significant changes in TCA were observed. T3 and free T4 increased transiently during the first month. After 12 months, 7 patients were hypothyroid (N = 3 in group I and N = 2 in groups II and III). rhTSH plus a 1.11-GBq fixed 131I activity did not cause acute or chronic changes in TCA. After 6 and 12 months, TV reduction was more pronounced among patients treated with rhTSH plus 131I.